„SPÓR O KOSĘ” W KONOPIELCE EDWARDA REDLIŃSKIEGO A ZMIENNE TREŚCI PERCEPCYJNE SCHEMATÓW POJĘCIOWYCH - Michał Rydlewski (Etnografia Polska, 2017)
In this article, I make an intellectual experiment which is focused on how people and their worldview are determined by culture. The text is centered around a well-known story called ‘conflict about a scythe’ contained in a Polish novel by Edward Redliński, Konopielka. Using ethnological and philosophical texts of A.P.Kowalski, M. Foucault, M.Mauss, I explain how our knowledge and the magical culture determine the way of thinking. I ask to what extend folk communities described in Konopielka are determined by the magical way of seeing the world. In my opinion, there is a strong magical echo in the folk society which makes it problematic to understand different interpretations of the ‘conflict about a scythe’ in Polish ethnological descriptions.